PENGEMBANGAN MEDIA KOTAK PROSES FOTOSINTESIS BERBASIS HOTS PADA MATERI FOTOSINTESIS TERHADAP IPA KELAS IV SDN UNYUR - Syachruroji, Ahmad; Andriana, Encep; Pinalar, Icha Kersa (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
Learning science for the elementary school level one that must be prioritized is how their curiosity and critical thinking power towards a problem. Therefore, science learning in elementary schools still uses the nature of science which consists of products, processes, and attitudes that lead students to solve problems. Natural Science (Science) is related to how to find out about nature systematically so that science is not only the mastery of a collection of knowledge in the form of facts, concepts, or principles. This study used the Research & Development (R&D) Method. The results of the research on the development of photosynthetic process media received 99% feasible to be used for learning ran about green plant material, then the response of students was very good to HOTS-based learning media.Â Based on the results of the study, it can be concluded that HOTS-based photosynthesis box media is suitable for use in elementary science learning